-48 -16 = 20
First add -48 and -16, which = -64, which indicates that this is not an equation, because both sides are not equal. -64 â‰ 20
the first step in solving the equation is to subtract the nine from the three. you will get negative 6.
The first step not possible in solving an equation algebraically is not to provide an equation in the first place in which it appears to be so in this case.
Subtract 1 form both sides of the equation
Combine the constants on one side. -4x = 36
The first step would be to find the equation that you are trying to solve!
add 2 to 22, then divide by 6. n= ? n= 4
The first step is produce the radical equation that needs solving.
t - 17 = 48 The first step is to move the -17 to the right side of the equation and end up with: t = 48 + 17. (When you switch sides, the sign changes) To solve the equation: t = 65
The first step is to solve one of the equations for one of the variables. This is then substituted into the other equation or equations.
Combine like terms
Get rid of the denominator.